Sevoflurane-induced neuronal apoptosis in neonatal mice is prevented with intranasal administration of insulin - Li, Hengchang (Am J Transl Res, 2020)
Concerns about the potential neurotoxicity of general anesthesia to the developing brain have been increasing in recent years. Animal studies have shown that neonatal exposure to general anesthesia causes both acute neurotoxicity and behavioral abnormalities later in life. In the present study, we observed over-activation of neuronal apoptosis in the brain of neonatal mice after a single exposure to anesthesia with sevoflurane for 6 hours at the age of 7 days. More importantly, we found that insulin administered through intranasal delivery prior to anesthesia prevented anesthesia-induced over-activation of neuronal apoptosis. This study provides experimental evidence for a potential effective, yet simple, method to prevent anesthesia-induced neurotoxicity in children, especially in infants.